Beyond Cat Scratch Disease: A Case Report of Bartonella Infection Mimicking Vasculitic Disorder. (8th August 2012) - Spinella, Amelia; Lumetti, Federica; Sandri, Gilda; Cestelli, Valentina; Mascia, Maria Teresa
Abstract : Cat scratch disease (CSD) is a bacterial disease caused by Bartonella henselae and it is mainly characterized by self-limiting lymphadenopathy in the draining site of a cat scratch or bite. We report a patient with history of fever, swelling lymph nodes, vasculitic-like skin lesions, and positivity of Bartonella serology initially considered as expression of a disimmune disease.